PGIS based land information mapping and map updating to support rural community knowledge building - Mulalu, M.; Veenendaal, Bert (2015)
This paper outlines an approach developed to assist a rural community in Botswana to utilise Geographic Information Systems (GIS) to compile and update a village land parcels dataset. The work is based on a PhD research work which was carried out at a remote rural village, where participatory action research was employed. Participation is defined as learning and the Participatory Geographic Information Science (PGIS) framework was considered to be appropriate. The contention here is that community learning is a pre-condition for successful implementation of human development interventions. The PGIS activity itself served mainly to anchor the learning of the creation of the database, the construction of knowledge and its contribution to improve individual household livelihoods. The rationale here is that the database design process can be devolved to ordinary language so that the attention is drawn more to the subsequent use of the data rather than to its compilation. Therefore the PGIS was envisaged as interacting objects and people, relations among them and the role of the containing space. It was also anticipated that in the process, the information would be conversed and the knowledge perceived, constructed and conceived.The basic essence of the PGIS approach was to use georeferenced digital colour aerial photographs and on screen digitizing (OSD) to create land parcels vectors and use the plotted land parcels as references to update the village plot layouts by measuring and scaling in the missing plots at the field. The GIS based mapping was preceded by entry and collaborative team building processes and basic training in computing, business process modeling, business calculations and business planning. This was followed by social survey focused on the poor and struggling members of the community. The produced PGIS artifact served to be the sink for all the produced data. The early conclusion that was drawn was that the PGIS serves as an effective instrument to help a rural community to create and construct knowledge and to strike the link with the political institutions that are intended to support citizens to improve their living standards.